Reading subjects: passbooks, literature and apartheid - Saint, Lily (Social dynamics, 2012)
Between 1916 and 1981, 17.25 million black South Africans were arrested for pass-law infringements. Though passbooks were pivotal texts in the lives of many South Africans, scholarship has focused mostly on their role in administering labour influxes. Thus the implications of having books facilitate state power have been largely unexplored. This article considers passbooks as books to examine how they narrated lives and conditioned various political and racial modes of subjectivity. It argues that despite passbooks' unparalleled control over South Africans' everyday lives, passbooks failed to mould all life stories into the rigid forms promulgated by apartheid doxa. Counter-narratives in black and 'coloured' writing of the period provide a useful framework for re-evaluating the role of reading and writing in the production of power. As interventions in the apartheid state's monopoly of public discourse, such writing insisted that there be alternative ways of writing the apartheid subject into the archive.